A Consultation on Higher Education in Africa A Report to the Ford Foundation and the Rockefeller Foundation - Coombe, Trevor; London Univ. (England). Inst. of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This report examines the state of higher education in Sub-Saharan Africa, focusing on issues of interest to philanthropic organizations seeking to assist African colleges and universities. Chapter 1 discusses the impoverished state of most African universities, due largely to economic and political decline at the national level, as well as opportunities for change and improvement, especially in South Africa. Chapter 2 looks at the work of the African Association of Universities and other representative bodies. Chapter 3 describes government-university relations, university governance, and student affairs, concentrating on the problems that African universities face in these areas and possible solutions. Chapter 4 addresses university management, discussing ways to reduce costs and enhance revenues. Chapter 5 examines research opportunities, postgraduate studies, staff development, academic publishing, library development, and information technology. Chapter 6 reviews research on higher education in Africa. Each chapter includes general and specific proposals for the improvement of higher education in Africa, including specific areas of need that can be addressed by donor organizations. (Contains approximately 180 references.) (MDM)
Availability: Office of Reports, The Ford Foundation, 320 East 43rd Street, New York, NY 10017.
Sponsoring Agency: Rockefeller Foundation, New York, NY.
Sponsoring Agency: Ford Foundation, New York, NY.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change Strategies; College Administration; College Libraries; Colleges; Donors; Educational Attitudes; Educational Improvement; Educational Needs; Educational Trends; Financial Problems; Foreign Countries; Government School Relationship; Higher Education; Philanthropic Foundations; Private Financial Support; Universities; Africa; Reports, Descriptive